Zea Mays flour / Ahmad Shakani Abdullah, Iklima Husna Abdul Rahim and Marry Tracy Pawan - Abdullah, Ahmad Shakani; Abdul Rahim, Iklima Husna; Pawan, Marry Tracy (Universiti Teknologi MARA, Sabah, 2020)
In today's society, there is a great demand for appreciating nutritional standards in which characterized by rising costs and often decreasing availability of raw material together with concern about environmental pollution. Consequently, there is a considerable emphasis on their recovery, recycling and upgrading wastes. The food industry produces large volumes of wastes, both solids and liquids, resulting from the production, preparation and consumption of food. Due to legislation and environmental reasons, the food and beverage industry is highly enforced to find an alternative use for the residual matter. The latest trends impacting the food industry include moves to reduce the huge amount of food waste, as consumers simultaneously adapt their habits in times of continuing austerity. In the last decades, consumers demand in the field of food production has changed considerably. Consumers believe that food contribute directly to their health. Therefore, the idea of using underutilized and waste food products was triggered, where the main ingredient is made of plants waste which is corn silk. It is an invention to transform plant waste to corn silk flour - Zea Mays Flour (ZMF) that benefit the society through its help of increasing food for the world. Furthermore, it can help to enhance global efforts towards food security, nutrition, dietary needs, as well as foster health and income generation. Recycling products using underutilized and waste food products also could help to sustain the environment. There is one fact that must be beared in inventors' mind that scientific research alone does not guarantee for a product to be successful in the market. The product invented should fit the taste and needs for the consumers as the market success rate is influenced by the degree of familiarity and acceptance toward the product being sold. Many of the today's food and beverage products are not intended merely to satisfy hunger and provide humans with necessary nutrients, as they aim to prevent nutrition related diseases and increase physical and mental well-being of consumers. Therefore, it is necessary for product development to explore which need that consumer are concerned about, so that the product could achieve success and market acceptance. The idea using food product using underutilized/waste product, corn silk become Zea Mays Flour (ZMF), is hoped will support the idea of sustainability, specifically ins steadily gaining more attention from many food producers worldwide, to save the environment while at the same time boost the business through reduction of costs and considerable amount of waste.